2022
DOI: 10.1038/s41419-022-04950-2
|View full text |Cite
|
Sign up to set email alerts
|

m6A methylated EphA2 and VEGFA through IGF2BP2/3 regulation promotes vasculogenic mimicry in colorectal cancer via PI3K/AKT and ERK1/2 signaling

Abstract: Exploring the epigenetic regulation mechanism of colorectal cancer (CRC) from the perspective of N6-methyladenosine (m6A) modification may provide a new target for tumor therapy. Analysis using high-throughput RNA-seq profile from TCGA found that the gene expression of Methyltransferase-like 3 (METTL3) was significantly upregulated among 20 m6A binding proteins in CRC, which was also validated in CRC cancer tissues and cell lines. Moreover, transcriptome sequencing in METTL3 knockdown cells using CRISPR/Cas9 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…Emerging evidence shows that m6A modification is associated with malignant phenotypes of tumors such as cell proliferation, differentiation, invasion and metastasis and functions as an oncogene in the development and progression of cancers ( 21 24 ). Similarly, the increased expression of METTL3 involved in regulating cell excessive proliferation, multidrug resistance, and distant metastasis in GC ( 25 27 ). Recent studies have shown that increased expression of METTL3 was associated with tumor cell glycolysis metabolism and sensitivity to glycolytic stress in hepatocellular carcinoma ( 28 ), and N(6)-methyladenosine regulates the glycolysis of cancer cells through PDK4 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence shows that m6A modification is associated with malignant phenotypes of tumors such as cell proliferation, differentiation, invasion and metastasis and functions as an oncogene in the development and progression of cancers ( 21 24 ). Similarly, the increased expression of METTL3 involved in regulating cell excessive proliferation, multidrug resistance, and distant metastasis in GC ( 25 27 ). Recent studies have shown that increased expression of METTL3 was associated with tumor cell glycolysis metabolism and sensitivity to glycolytic stress in hepatocellular carcinoma ( 28 ), and N(6)-methyladenosine regulates the glycolysis of cancer cells through PDK4 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In reality, this signaling activates certain genes in surrounding the normal host tissue that causes proteins, such as proangiogenic factors, to encourage the growth of new blood vessels of solid tumors [17]. Vascular endothelial growth factor (VEGF), a proangiogenic factor, is a key mediator for the proper tumor vessel development, in which it is upregulated by oncogene expression, growth factors, and hypoxia [18][19][20]. VEGF mediates vascular EC survival, permeability, proliferation, and migration by binding and activating autophosphorylation of the tyrosine kinase receptors (VEGFR-2) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies [33][34][35] , IGF2BP3 has been recognized as an m6A reader that regulates m6A-modi ed genes, which led us to hypothesize that STRIP2 regulates IGF2BP3-dependent gene in an m6Adenpendent manner. To test this hypothesis, we rst identi ed the potential m6A-modi ed site of TMBIM6 based on RMVar database (https://rmvar.renlab.org/) and the results showed that the 3'-UTR of TMBIM6 has an m6A site (Fig.…”
Section: Resultsmentioning
confidence: 82%